Profile and Migration of Members of Residency Programs in Family Medicine - Ana Paula Tussi Leite; Scheila Mai; Alice Paul Waquil; Elvira Alicia Aparicio Cordero; Vitória Silva da Rosa; Carmen Vera Giacobbo Daudt; Brenda Wander; Maria Eugênia Bresolin Pinto; Isabel Brandão Correia; Thiago Dias Sarti (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To describe the sociodemographic profile and analyze the migratory characteristics of the members of the Residency Programs in Family Medicine in 2020 in Brazil. METHODS The study follows a cross-sectional observational design of a quantitative nature from the perspective of the members of the Residency Programs in Family Medicine. Questionnaires adapted for each participating group were developed, applied through an online platform. RESULTS Most participants are female and white. Most supervisors and preceptors were residents of Residency Programs in Family Medicine, however, there are some who are not specialists in the field. Most participants are based in capitals or metropolitan regions. In relation to retention, 41.1% of supervisors and 73.1% of preceptors are affiliated to a program in the same municipality where they lived. For most resident physicians, the place of residence coincides with the place of birth and/or graduation (57.4%), and 48.5% are in the same place of graduation. CONCLUSIONS The research reinforces the need for policies to promote the migration of residents to Residency Programs in Family Medicine outside capital cities and metropolitan regions, as well as encouraging the retention of graduates trained outside large urban centers so that they can contribute to distribution and provision of doctors where they are still needed.